Fremanezumab for the preventive treatment of migraine in adults. Issue 8 (3rd August 2019) - Lionetto, Luana; Curto, Martina; Cisale, Giusy Ylenia; Capi, Matilde; Cipolla, Fabiola; Guglielmetti, Martina; Martelletti, Paolo
ABSTRACT: Introduction : The Calcitonin Gene-Related Peptide (CGRP) has been implicated in migraine pathophysiology due to its role in neurogenic inflammation and transmission of trigeminovascular nociceptive signal. New molecules targeting CGRP and its receptor have been developed as migraine-specific preventative treatments. Fremanezumab (or TEV-48, 125, LBR-101), a human monoclonal antibody against CGRP, has been recently approved for clinical use by FDA and EMA. Areas covered : This paper briefly discusses the calcitonin family of neurotransmitters and resultant activation pathways and in-depth the chemical properties, pharmacodynamics, pharmacokinetics, clinical efficacy and safety of Fremanezumab for the prophylactic treatment of migraine. Expert opinion : Fremanezumab, a migraine-specific drug, is effective and safe as a prophylactic treatment of chronic and episodic migraine. As a monoclonal antibody, it was not associated to liver toxicity and is not expected to interact with other drugs. The long half-life might improve patients' compliance. Long-term effects of CGRP block in cardiovascular, grastrointestinal and bone functions should be evaluated in ongoing trials, since CGRP is involved in multiple biological activities in the human body. Nevertheless, targeting CGRP itself allows the receptor binding with other ligands involved in several physiological functions. Thus, the long-term treatment with Fremanezumab is expected to be associated with a lower risk of severe adverse effects.